The effect of stronger intellectual property protection on technological innovation in developing countries: the case of Lesotho - Leseeo, Mapitso (School For Advanced Legal Studies, 2026)
Intellectual property (IP) is one of the legal subjects which is increasingly receiving attention, but about which little is generally known outside specialised legal circles. 1 This is because IP in itself has always been an integral part of the general economic social and cultural development worldwide.2 This begs the question: What is intellectual property? IP refers broadly to a number of distinct types of creations of the human mind, for which property rights are recognised. Its influence extends to every aspect of life because it cuts across all disciplines.